Extranodal Rosai-Dorfman Disease Involving Colon A Case Report with Review of the Literature - Chen, MD, Haiying; Sun, MD, PhD, Jianlan; Aftab, MD, Lalarukh; Sands, MD, Amy (North American Journal of Medicine and Science, 2010)
Rosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy, is a rare, idiopathic and non-neoplastic histiocytic disorder. The most common presentation of RDD is painless cervical lymphadenopathy in a young patient. However, in about 25% of cases there is no lymph node involvement, and the disease presents as a mass in skin, soft tissue, nasal cavity, eye, bone, or other extranodal sites (extranodal type). This can pose a diagnostic challenge if RDD is not considered in differential diagnoses. Gastrointestinal (GI) involvement of RDD is extremely rare; only 15 cases had been reported. We report a case of extra-nodal RDD involving the GI tract of a 24-year-old African-American woman who presented with chronic lower abdominal pain, constipation and an 8 cm mass involving her colonic wall. Microscopically, the mass was well demarcated, partially covered with serosa and extended into the muscularis propria and submucosa of the colon. The lesional cells consisted of spindle-shaped and epithelioid histiocytes intermixed with plasma cells and lymphocytes. Rare histiocytes showed emperipolesis. The histiocytes were positive for S100 (strong) and CD68, and negative for c-kit and CD1a. The above morphological and immunohistochemical features are diagnostic for RDD, extra-nodal type. The related literature was reviewed and compared with this case.